Use and accidental exposure to hallucinogenic agents reported to the Czech Toxicological Information Centre from 1995 to 2008 - Mrazova, Karolina; Navratil, Tomas; Pelclova, Daniela (Substance use & misuse, 2011)
Intoxication by hallucinogenic agents is relatively common in the Czech Republic, with most cases of the use of these agents being by adolescents and young people. The objective of the study was to evaluate the number, trends, gender and age of the subjects, and the severity of exposure in intoxication by hallucinogenic plant and mushroom substances, in comparison with synthetic drugs, brought to the attention of the Toxicological Information Centre (TIC) through inquiries over the past 14 years (1995-2008) (from total 3,702 calls concerning the use of both natural and synthetic drugs, 917 calls were due to the use of hallucinogenic plants and mushrooms).
Keywords: dospělí; Chi-Square Distribution; toxikologická centra; Female; Hallucinogens; Age Factors; Adult; ženské pohlaví; Adolescent; věkové faktory; halucinogeny; lidé; rostliny; Sex Factors; Male; sexuální faktory; Czech Republic; Agaricales; rozdělení chí kvadrát; Plants; Česká republika; Poison Control Centers; mužské pohlaví; mladiství; Humans